2015
DOI: 10.1017/cem.2015.4
|View full text |Cite
|
Sign up to set email alerts
|

Mental practice: a simple tool to enhance team-based trauma resuscitation

Abstract: Introduction: Effective trauma resuscitation requires the coordinated efforts of an interdisciplinary team. Mental practice (MP) is defined as the mental rehearsal of activity in the absence of gross muscular movements and has been demonstrated to enhance acquiring technical and procedural skills. The role of MP to promote nontechnical, team-based skills for trauma has yet to be investigated. Methods: We randomized anaesthesiology, emergency medicine, and surgery residents to two-member teams randomly assigned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
61
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 20 publications
0
61
0
5
Order By: Relevance
“…24 Another recent RCT studied the effects of imagery on emergency, anesthesia, and surgery residents' teamwork (i.e., assessed by expert raters using the Mayo High Performance Teamwork Scale: MHPTS) during a simulated trauma resuscitation scenario. 25 The authors found that the imagery group significantly outperformed controls in teamwork, and concluded that imagery is an effective tool to increase team-based skills. In another recent study of the effects of guided mental imagery on residents' performance on two methods of simulated LCs (i.e., physical task on a torso trainer and VR simulator), Paige et al (2015) found that imagery was related to improved performance of a VR two-hand clip-and-cut task.…”
Section: Mental Imagerymentioning
confidence: 99%
See 1 more Smart Citation
“…24 Another recent RCT studied the effects of imagery on emergency, anesthesia, and surgery residents' teamwork (i.e., assessed by expert raters using the Mayo High Performance Teamwork Scale: MHPTS) during a simulated trauma resuscitation scenario. 25 The authors found that the imagery group significantly outperformed controls in teamwork, and concluded that imagery is an effective tool to increase team-based skills. In another recent study of the effects of guided mental imagery on residents' performance on two methods of simulated LCs (i.e., physical task on a torso trainer and VR simulator), Paige et al (2015) found that imagery was related to improved performance of a VR two-hand clip-and-cut task.…”
Section: Mental Imagerymentioning
confidence: 99%
“…Imagery has been shown to be a cost-effective training supplement to physical practice that cuts down on resource consumption, [12][13]17,23,29,31 and enhances surgeons' performance through improved acquisition and performance of surgical skills, [13][14][15][16][18][19]22,24,[29][30] knowledge, 11,23,26 confidence, 23,[26][27] and team-based skills. 25 …”
Section: Mental Imagerymentioning
confidence: 99%
“…''Mental rehearsal'' or ''cognitive imaging'' allows the opportunity to think through both procedural and crisis management aspects of airway management before intubation. 17,18 This mirrors the preparation by an elite athlete who pre-plans an upcoming ski race or penalty kick or by a pilot who is taught to ''fly ahead of the plane''. Indeed, true airway experts should ensure that patient management, and team performance, never extend beyond where their mind has not already been.…”
mentioning
confidence: 99%
“…Regardless, these guidelines also reflect our growing awareness that the potential for errors is common and ubiquitous and far less likely to be a random unpredictable event. 4,17,18 Modernizing our understanding of human errors and airway management…”
mentioning
confidence: 99%
See 1 more Smart Citation